Experimental and Theoretical Performance Evaluation of a Solar Passive Featured Envelope Building in Composite Climate - et. al., Dr. Mahendra Joshi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The performance of School of Energy and Environmental Studies (SEES) building a solar passive envelope building at Indore India has been analyzed by experimental measurements of air and surface temperatures . For the analysis the data for peak winter (December) and peak summer (June) months only was used. Further from the building, data for two rooms in south block (a classroom and library) and two rooms in north block (environment lab and class room) facing opposite to each other were used to compare the thermal performance of south and north units. The surface temperatures of library were also used to measure the thermal time lag due to the hollow wall. Thermal simulation and analysis package TRNSYS was used to simulate the building for air and surface temperatures and the results are validated using the measured data. It has been found that in the month of June the minimum surface temperature occurred at 5.00am in the morning while, the minimum ambient temperature was recorded at 6.00am and in the month of December the minimum of both surface temperature and ambient temperature occurred at 6.00am in the morning. It is also found from that a time lag of about 4 hours between the maximum of the outer and inner surface of the south wall of library during the month of June and a time lag of 2 hours between the minimum temperatures of the outer and inner surface of the wall was observed during the month of June..